Impact of Smartphone Addiction on Neck Pain Among University Students: Smartphone Addiction and Neck Pain - Shanzay Khan; Bhawna Kumari; Sandhya Kataria; Ramsha Sultan; Aisha Hakim; Quratulain; Aqsa Faiz; Sheza Mazhar; Aslam, Intsam (Journal of Health and Rehabilitation Research, 2024)
Background: Smartphone addiction is increasingly common among university students and has been linked to musculoskeletal issues, particularly neck pain, due to prolonged improper postures. This study aimed to investigate the impact of smartphone addiction on neck pain among university students. Objective: To evaluate the relationship between smartphone addiction and neck pain among university students. Methods: A cross-sectional study was conducted from January to June 2023 among 219 university students aged 18-35. Data were collected using the Smartphone Addiction Scale-Short Version (SAS-SV) and the Neck Disability Index (NDI). Convenience sampling was used, and exclusion criteria included neurological disorders, prior neck surgeries, or musculoskeletal diseases. Ethical approval was obtained following the Helsinki Declaration. Data were analyzed using IBM SPSS version 25. Chi-square tests and multivariate analysis were applied to assess associations, with a significance level of p < 0.05. Results: 34.2% of participants reported neck pain related to smartphone use. Among them, 43.8% experienced mild pain while reading on smartphones. The NDI showed that 15.1% had moderate pain, while 4.1% experienced fairly severe pain. Conclusion: Excessive smartphone use is significantly associated with neck pain among university students. Preventive strategies and ergonomic awareness are recommended to reduce neck strain.